Association between residence near surface coal mining and blood inflammation. Issue 2 (April 2015) - Hendryx, Michael; Entwhistle, Jennifer
Highlights Adjusted C-reactive protein is elevated for adults living near surface coal mines. Counts of ambient particulate matter are higher in mining communities. Self-reported health indicators are worse in mining communities. All participants were non-smokers and non-miners without acute illness.